Myeloid-derived suppressor cells in cancer: therapeutic targets to overcome tumor immune evasion - Junli Lu; Yiming Luo; Dean Rao; Tiantian Wang; Zhen Lei; Xiaoping Chen; Bixiang Zhang; Yiwei Li; Bifeng Liu; Limin Xia; Wenjie Huang (Experimental Hematology & Oncology, 2024)
Abstract Paradoxically, tumor development and progression can be inhibited and promoted by the immune system. After three stages of immune editing, namely, elimination, homeostasis and escape, tumor cells are no longer restricted by immune surveillance and thus develop into clinical tumors. The mechanisms of immune escape include abnormalities in antitumor-associated immune cells, selection for immune resistance to tumor cells, impaired transport of T cells, and the formation of an immunosuppressive tumor microenvironment. A population of distinct immature myeloid cells, myeloid-derived suppressor cells (MDSCs), mediate immune escape primarily by exerting immunosuppressive effects and participating in the constitution of an immunosuppressive microtumor environment. Clinical trials have found that the levels of MDSCs in the peripheral blood of cancer patients are strongly correlated with tumor stage, metastasis and prognosis. Moreover, animal experiments have confirmed that elimination of MDSCs inhibits tumor growth and metastasis to some extent. Therefore, MDSCs may become the target of immunotherapy for many cancers, and eliminating MDSCs can help improve the response rate to cancer treatment and patient survival. However, a clear definition of MDSCs and the specific mechanism involved in immune escape are lacking. In this paper, we review the role of the MDSCs population in tumor development and the mechanisms involved in immune escape in different tumor contexts. In addition, we discuss the use of these cells as targets for tumor immunotherapy. This review not only contributes to a systematic and comprehensive understanding of the essential role of MDSCs in immune system reactions against tumors but also provides information to guide the development of cancer therapies targeting MDSCs.